Pertimbangan Hakim terhadap Pembatalan Putusan BPSK: Studi Putusan Mahkamah Agung 553/K-Pdt.Sus-BPSK/2025 - Angela, Silvia; Lie, Gunardi (Riwayat: Educational Journal of History and Humanities, 2025)
This study examines the procedural irregularities that led to the annulment of the Consumer Dispute Settlement Agency (BPSK) decision in the Supreme Court Judgment No. 553/K-Pdt.Sus-BPSK/2025. The research was motivated by the increasing number of consumer disputes in digital transactions and the recurring inconsistency in BPSK decisions, particularly regarding violations of procedural fairness. Using a normative legal research method, the analysis draws upon statutory regulations, court decisions, and legal doctrine to assess whether the dispute resolution process conducted by BPSK aligned with the principles of consumer protection law. The findings reveal that BPSK failed to comply with essential procedural standards, including improper summons to the business actor, the absence of valid consent for arbitration, and reliance on outdated legal provisions. These errors resulted in the violation of due process and the principle of audi et alteram partem, ultimately undermining the legitimacy of BPSKs decision. The study further demonstrates that such procedural defects harm both consumers and business actors, weaken legal certainty, and diminish the credibility of BPSK as an alternative dispute resolution institution. The research concludes that strengthening procedural compliance, ensuring consistent application of legal norms, and enhancing institutional competence are crucial for improving the effectiveness of consumer dispute resolution and safeguarding public trust in BPSK